2016
DOI: 10.1007/s00402-016-2523-8
|View full text |Cite
|
Sign up to set email alerts
|

Two stage reconstruction versus bone transport in management of resistant infected tibial diaphyseal nonunion with a gap

Abstract: The use of two stage reconstruction in cases of resistant infected tibial diaphyseal nonunion gives comparable results to the Ilizarov ring external fixator in cases associated with bony defects within the confines of 6 cm with superiority in preservation of ankle and subtalar joints range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
0
27
1
Order By: Relevance
“…In our study, the mean external fixation index was 1.43 months/cm, and the complications was 1.9 per patient; this was quite similar with the results by Paley and Maar [ 19 ] ; their study consisted of 19 patients, the result showed 22 minor and 19 major complications, and the complications were 2.2 per patient. Our results showed an obviously higher complication rate when compared with previous literature, [ 4 , 5 , 8 , 9 , 19 ] whereas all of patients in this study suffered tibial infected nonunion, experienced with multiple previous treatment failures, even in the presence of poor soft tissue coverage; this was an obvious difference from aforementioned studies. Pin-track infection was the most frequently observed complication in the course of bone transport in previous reports, [ 4 , 5 , 8 , 9 , 19 ] and this complication was also noted frequently in our study without a negative impact on the final outcome.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study, the mean external fixation index was 1.43 months/cm, and the complications was 1.9 per patient; this was quite similar with the results by Paley and Maar [ 19 ] ; their study consisted of 19 patients, the result showed 22 minor and 19 major complications, and the complications were 2.2 per patient. Our results showed an obviously higher complication rate when compared with previous literature, [ 4 , 5 , 8 , 9 , 19 ] whereas all of patients in this study suffered tibial infected nonunion, experienced with multiple previous treatment failures, even in the presence of poor soft tissue coverage; this was an obvious difference from aforementioned studies. Pin-track infection was the most frequently observed complication in the course of bone transport in previous reports, [ 4 , 5 , 8 , 9 , 19 ] and this complication was also noted frequently in our study without a negative impact on the final outcome.…”
Section: Discussioncontrasting
confidence: 77%
“…Currently, Ilizarov reconstructions, the Masquelet technique, vascularised and non-vascularised bone grafts and bone substitutes are the main methods to treat tibia defects [2,8,9,[17][18][19][20][21][22]. However, bone transfer is the preferred technique for the treatment of infected tibial bone defects [1,4,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…At present, Ilizarov reconstructions, Masquelet technique, vascularised and non-vascularised bone grafts and bone substitutes are the main methods for tibia defects. [2,8,9,[17][18][19][20][21][22] However, bone transfer is the preferred technique for the treatment of infected tibial bone defects. [1,4,23,24] Ilizarov reconstructions techniques includes two main clinical treatment protocols: bone transport (BT) and acute shortening gradual lengthening (ASD).…”
Section: Discussionmentioning
confidence: 99%